2010
DOI: 10.2131/jts.35.577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidacloprid on antioxidant enzymes and lipid peroxidation in female rats to derive its No Observed Effect Level (NOEL)

Abstract: -Technical imidacloprid was evaluated for its effect on oxidative stress and Lipid peroxidation (LPO) in female rats for No Observed Effect Level (NOEL). Activities of Superoxide dismutase (SOD), Catalase (CAT), Glutathione peroxidase (GPx), and level of Glutathione (GSH) and LPO were estimated in liver, kidney and brain of rats after oral administration of imidacloprid (5, 10, 20 mg/kg/day) for 90 days. Imidacloprid at 5 and 10 mg/kg/day has not produced changes in SOD, CAT, GPx and level of GSH and LPO in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
45
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 25 publications
15
45
2
1
Order By: Relevance
“…These results are consistent with the findings [42] after oral administration of 20 mg/kg body weight/day of IMI for 90 days to female rats. Moreover, Ince et al [19] indicated that IMI treatment significantly increased MDA levels accompanied by concomitant depletion in liver SOD and CAT activities in mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the findings [42] after oral administration of 20 mg/kg body weight/day of IMI for 90 days to female rats. Moreover, Ince et al [19] indicated that IMI treatment significantly increased MDA levels accompanied by concomitant depletion in liver SOD and CAT activities in mice.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, enzymatic antioxidants including SOD and CAT are important parameters of antioxidant defenses system to inactivate the reactive oxygen species (ROS) produced by environmental contaminants [40]. They constitute the primary antioxidant enzymes and first lines of defense against the oxyfree radicals in cell [41,42]. In this investigation, it has a statistically significant decrease in SOD and CAT activities in hepatic tissues, which may be related to response to increased oxidative stress after IMI treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Oxidative stress is a part of IMI toxicity that has been evidenced by earlier studies (16)(17)(18)(19). Our study has added to this knowledge by showing that IMI toxicity varies with sex, tissue, and exposure duration.…”
Section: Resultssupporting
confidence: 67%
“…Many studies have shown the oxidative and neurotoxic potential of IMI in a variety of animal species, including rats (12)(13)(14)(15)(16)(17)(18)(19). However, none has investigated how biotransformation affects prooxidative and neurotoxic effects of IMI in mammals and whether it depends on sex, tissue, or exposure duration.…”
mentioning
confidence: 99%
“…Increasing use of pesticides and their potential toxic effects among humans and animals warrant a heightened awareness about these chemicals (David et al, 2007;Kapoor et al, 2010) Hence, pesticides still pose a major problem in toxicology (Askar et al, 2011). The previous reports showed that permethrin (PM) was a highly toxic synthetic pyrethroid pesticide widely used in agriculture aquatic organisms and vector control programs (Vadhana et al, 2010;Fojut and Young, 2011;Srivastava et al, 2006).…”
Section: Introductionmentioning
confidence: 99%